Natural Resources and Conflict: A Dispute of Kurds and the Iraqi Government in Kirkuk - Nurdiansah, Nandang (Middle Eastern Culture & Religion Issues, 2023)
The conflict between the Kurds and the Iraqi government in Kirkuk is not just a political conflict. This article describes how oil resources in Kirkuk can trigger conflict between the Kurds and the Iraqi government. The clash of interests between the two parties is crucial to overcome. The Kurdish referendum support group is determined to depart. Meanwhile, the government defends the Kirkuk region due to its rich natural resources. As a tool for analyzing events, the approach used is the theory of natural resources and violent conflict proposed by Ian Bannon and Paul Collier. The results indicated that Iraq's dependency and weak management of oil export commodities caused the conflict between the Kurds and the Iraqi government. This article, compiled by applying the literature review method, aims to explain the conflict in the Kirkuk region, with natural resources as the object also the Kurds and the Iraqi government as subjects facing each other.